Microtextured CoCrMo alloy for use in metal-on-polyethylene prosthetic joint bearings: Multi-directional wear and corrosion measurements. (August 2018) - Langhorn, J.; Borjali, A.; Hippensteel, E.; Nelson, W.; Raeymaekers, B.
Abstract: The longevity of metal-on-polyethylene (MoP) prosthetic hip joint bearings, in which a polished CoCrMo femoral head articulates with a polyethylene liner, may be limited by mechanical instability or inflammation resulting from osteolysis caused by polyethylene wear debris. This study uses laser surface texturing to manufacture a pattern of shallow spherical microtexture features on a polished CoCrMo surface. Gravimetric wear measurements of a highly-crosslinked polyethylene pin articulating with a CoCrMo disc under multi-directional shear demonstrate that polyethylene wear is reduced by more 50% when articulating with a microtextured as opposed to a polished CoCrMo disc. Electrochemical measurements also show that laser texturing does not negatively affect the corrosion potential of CoCrMo. Highlights: Microtextured CoCrMo reduces polyethylene wear more than 50% compared to polished CoCrMo surfaces. A CoCrMo surface treated with laser surface texturing retains identical corrosion resistance as the non-textured CoCrMo surface. An elastohydrodynamic lubrication model simulates the effect of microtexture design on lubricant film thickness.